Challenges and best practices for hepatitis C care among people who inject drugs in resource limited settings: focus group discussions with healthcare providers in Kenya. Issue 12 (2nd December 2022) - Seu, Rie; Riback, Lindsey R.; Nyakowa, Mercy; Lizcano, John; Musyoki, Helgar; Ross, Jonathan; Cherutich, Peter; Kurth, Ann E.; Akiyama, Matthew J.
ABSTRACT: People who inject drugs (PWID) living with Hepatitis C (HCV) in low- and middle-income countries face substantial barriers to HCV care. We sought to gain healthcare providers' perspectives on challenges and best practices for HCV care provision among PWID in Kenya. We conducted three focus group discussions (FGD) with 23 healthcare providers working with PWID living with HCV in Nairobi and Mombasa. Transcribed interviews were analysed thematically. Overarching themes regarding HCV prevention and treatment were: (1) lack of HCV-related knowledge at the provider and patient levels; (2) stigmatisation of people living with HCV and PWID; and (3) difficulties among PWID with navigating the healthcare system. Some providers suggested systematically integrating HCV care into existing PWID-specific harm reduction programs to improve HCV care provision as well as creating national HCV guidelines to guide clinicians. This study highlights the need for national HCV treatment guidelines and increased public HCV education, as well as culturally sensitive models integrating HCV care into programs PWID are already accessing. These strategies will be useful in improving access to HCV care among PWID and has the potential to decrease HCV transmission and prevalence among this vulnerable population.